Control over conflict during movement preparation: role of posterior parietal cortex. - Coulthard, E; Nachev, P; Husain, M (2008)
Flexible behavior in humans often requires that rapid choices be made between conflicting action plans. Although much attention has focused on prefrontal regions, little is understood about the contribution of parietal cortex under situations of response conflict. Here we show that right parietal damage associated with spatial neglect leads to paradoxical facilitation (speeding) of rightward movements in the presence of conflicting leftward response plans. These findings indicate a critical role for parietal regions in action planning when there is response competition. In contrast, patients with prefrontal damage have an augmented cost of conflict for both leftward and rightward movements. The results suggest involvement of two independent systems in situations of response conflict, with right parietal cortex being a crucial site for automatic activation of competing motor plans and prefrontal regions acting independently to inhibit action plans irrelevant to current task goals.